Inhibitory effects of lactobacilli of goat's milk origin against growth and biofilm formation by pathogens: an in vitro study. (April 2018) - Singh, Niharika; Sharma, Chetan; Gulhane, Rohini Devidas; Rokana, Namita; Singh, Brij Pal; Puniya, Anil Kumar; Attri, Sampan; Goel, Gunjan; Panwar, Harsh
Abstract: This study investigated the effects of lactic acid bacteria (LAB) of goat's milk origin on growth and biofilm formation of two pathogenic strains viz. Pseudomonas aeruginosa and Staphylococcus aureus . Different LAB preparations such as untreated cell free supernatants (CFSs), pH neutralized CFS (N-CFS) and heat treated CFS (H-CFS) of lactobacilli were screened for their antimicrobial and biofilm inhibitory properties. The antagonistic activities were compared to L . acidophilus, a reference probiotic strain. In addition, metabolic activity of bacterial pathogens upon CFSs challenge was also determined by MTT assay. LAB CFSs inhibited pathogen growth to a varied degree. A decrease in the number of sessile pathogen cells was observed upon exposure with untreated CFS, under both post and co-incubation strategy. The CFS of GM12, GM13, GM15 and GM17 could effectively inhibit the biofilm formation of both the pathogens to a significant level (p < 0.05) varying between 72% and 86%. Upon principal component analysis of recorded data, untreated CFS from GM12 emerged to be most promising against both the test biofilm formers. N-CFS and H-CFS preparations also limited the biofilm formation, however to a lower extent than untreated form. As also determined by MTT assay, the metabolic activity of P. aeruginosa and S. aureus were significantly reduced upon CFS exposure. The light microscopic images depicted major disruption in the biofilm matrix of pathogenic strains upon CFS challenge. Findings from this study indicate that the Lactobacillus strains of goat milk origin screened in this study may serve as bio-control agents for prophylactic use to prevent infections.